The Ideological Origins of "Written" Constitutionalism. - SIDDIQUE, ASHEESH KAPUR (Early American Studies, An Interdisciplinary Journal)
Americans have long argued that during the Age of Revolutions, the "early modern" world became "modern" thanks to a set of political innovations in the nature of government. Paramount among these was the creation of nation-states founded on the "invention" of written constitutions-beginning with the new United States, whose form of written constitutionalism served as a model for other polities. This article challenges that narrative. Building on recent scholarship on the coproduction of writing practices and state formation, it argues that the mode of constitution-making inaugurated in the aftermath of the American Revolution represented less a moment of origin than an ideological project of revising the relationship between document and statecraft characteristic of the early modern British Empire. Early American elites sought to portray the written constitution of empire as archaic as they defined their own species of written constitutionalism as an innovation, one they posited as the template for a normative form of the "modern" state.